Membrane Engineering for Biogas Valorization - Brunetti, Adele; Barbieri, Giuseppe (Frontiers in Chemical Engineering, 2021)
Membrane operations nowadays drive the innovative design of important separation, conversion, and upgrading processes, and contribute to realizing the main principles of “green process engineering” in various sectors. In this perspective, we propose the re-design of traditional plants for biogas upgrading and integrating and/or replacing conventional operations with innovative membrane units. Bio-digester gas streams contain valuable products such as biomethane, volatile organic compounds, and volatile fatty acids, whose recovery has important advantages for environment protection, energy saving, and waste valorization. Advanced membrane units can valorize biogas by separating its various components, and establishing environmentally friendly and small-scale energivorous novel separation processes enables researchers to pursue the requirements of circular economy.